A Study Of The Relationship Between The Determinants Of Service Quality In The Hospitality Industry With Special Reference To The Coimbatore District - SWAMIDOSS, S. BERNARD EDWARD; VENKATESAN, Dr. G. (The journal of contemporary issues in business and government, 2021)
The study’s goal is to look into the connection between administration efficiency and customer satisfaction in the hospitality industry. The SERVQUAL concept was used to keep track of the inquiry. Purposive checking was used in the investigation, which yielded 235 valid responses using the research methodology. The findings revealed that physical properties, empathy, and openness, three components of the SERVQUAL paradigm, have a supportive and vital interaction with clients. In either case, customer satisfaction was negatively affected by dependability and validation.